Kualitas Pelayanan BPJS di RSUD Kab. Karanganyar (Studi Kasus Pasien Rawat Inap) - Sastika Candra Paramashantaty; Nina Widowati (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
Social Security Agency of Health (BPJS) is a State-Owned Enterprises were specially commissioned by the government to administer health care benefits for all Indonesian people. In order to meet public demand for Karanganyar, Hospital District. Karanganyar has a mission to provide quality health services and affordable by the community in accordance with Law No. 23 of 1999 concerning health services. In improving the health care needs of the community in accordance with the maximum of the need for Community Satisfaction Survey in the services provided Hospital District. Karanganyar against patients on BPJS especially hospitalization. The survey in accordance with the Regulation of the Minister of Administrative Reform and Bureaucratic Reform No. 16 of 2014 on Guidelines for Public Satisfaction Survey Of Public Service Operator. The regulation covers the nine elements of community satisfaction with services including the requirements, procedures, time of service, fees or tariffs, product specifications types of service, executive competence, executive behavior, notice of service and complaint handling suggestions and feedback. The purpose of this study was to determine the level of Community Satisfaction BPJS patients about the services provided by hospitals Karanganyar and elements that inhibit community satisfaction with services Karanganyar District Hospital. The method used is descriptive quantitative research methods. Meanwhile, to analyze the data using the average or mean, frequency distribution and graphs. The results of this study explains that the level of community satisfaction with services provided by the Hospital District. Karanganyar is good and the elements that hinder the satisfaction of the people earn less good score includes the procedures, time of service, product specifications types of service, executive competence, as well as implementing behavior. Based on these results, it is suggested that the District Hospital. Karanganyar maximize again in providing services as well as add Human Resources to make it faster and coordinated. And apply the principles of greetings, greetings and well groomed is one of support maximum performance in providing services.